2018
DOI: 10.1088/1674-1056/27/11/110503
|View full text |Cite
|
Sign up to set email alerts
|

Some new advance on the research of stochastic non-smooth systems

Abstract: Due to the extensive applicability in real life, the non-smooth system with random factors attracted much attention in past two decades. A lot of methods and techniques have been proposed to research these systems by scholars. In this paper, we will summarize some new research advance on the stochastic non-smooth systems. The existing results about the stochastic vibro-impact system, the stochastic friction system, and the stochastic hysteretic system are introduced respectively. Some conclusions and outlook a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 111 publications
0
7
0
Order By: Relevance
“…Due to the discontinuities, the systems display some distinctive features that are quite different from the smooth cases. In recent years, this interesting topic [6][7][8][9][10][11][12][13] has been paid considerable attentions. In this work, we focus on some specific systems that are modelled by stochastic differential equations (SDEs) with piecewisesmooth drifts.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the discontinuities, the systems display some distinctive features that are quite different from the smooth cases. In recent years, this interesting topic [6][7][8][9][10][11][12][13] has been paid considerable attentions. In this work, we focus on some specific systems that are modelled by stochastic differential equations (SDEs) with piecewisesmooth drifts.…”
Section: Introductionmentioning
confidence: 99%
“…Through the study of actual mechanical engineering problems, it is found that the treatment of non-smooth systems under noise disturbance is often a big hassle [1][2][3]. Different types of mechanical systems, such as hydraulic safety valves, aircraft wings, energy harvesting, flexible manipulator with clearance, rotor-stator interactions in turbines and so on, will inevitably produce non-smooth dynamics [4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…However, friction produces strong and non-smooth nonlinearity, which significantly changes the performance of the original system. 8…”
Section: Introductionmentioning
confidence: 99%
“…However, friction produces strong and non-smooth nonlinearity, which significantly changes the performance of the original system. 8 Quite a few models have been established for friction, such as the Coulomb friction model, the Stribeck friction model, 9 and the LuGre model. 10 The Coulomb friction model is the simplest and has been extensively employed, especially for dry friction.…”
Section: Introductionmentioning
confidence: 99%